3-year data of the refugee child mental health unit - (:unkn) unknown (KLINIK PSIKIYATRI DERGISI, 2021)
Objective: It is known that refugee children and adolescents are at risk in terms of susceptibility to mental illnesses. It will be important to recognize the mental problems of this disadvantaged group in an early period and to serve appropriate treatment approaches with addressing quicly the risk factors and develop necessary strategies. In our study, it was aimed to review the data of a specialized Refugee Child Mental Health Unit to provide mental health services to refugee children and adolescents. Method: Data on sociodemographic characteristics, educational status, diagnoses made according to DSM-5 classification system, follow-up processes and treatments of children and adolescents who applied to the refugee outpatient clinic between 2017-2020 were analyzed. Results: The sample of our study consisted of 156 children and adolescents (n=50, 32.1% girls; n=106, 67.9% boys) with a mean age of 10.8 +/- 2.9 years. It was learned that 104 of the children (66.7%) went to school, but 65.7% (n=69) of those did not attend at school regularly. It was observed that almost half of the outpatient clinic applications (n=68, 43.6%) did not come to the follow-up appointments given after the first interview. The most common diagnoses are attention deficit hyperactivity disorder (n=42, 26.9%), post-traumatic stress disorder (n=42, 26.9%), major depressive disorder (n=39, 25%), and anxiety disorders (n=36, 23.1%). It was observed that 13 (8.3%) patients applied to the outpatient clinic after exposure to sexual abuse. Discussion: The results of our study showed that refugee children complain of many mental illnesses, and it was thought that increasing the health and education opportunities available to them and developing policies specific to our country in these areas would be protective in terms of mental health for this particular group.
Keywords: Refugee; child; PTSD; ADHD; sexual abuse; depression; migration; CARE; GUIDANCE; VIOLENCE